2021
DOI: 10.1093/eurpub/ckab165.601
|View full text |Cite
|
Sign up to set email alerts
|

Organization of mental health services to face COVID-19 in Brazil

Abstract: Issue/problem Covid-19 pandemic requires rapid responses. The reconfiguration of the psychosocial care network was needed to ensure access to all patients during this period. Description of the problem Psychosocial Care Centers (PCC) are strategic equipment for strengthening the mental health policy in Brazil. These services work with a multi and interdisciplinary team, aiming to assist crisis and rehabilitation processes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Concerning mental healthcare strategies, as reported in the literature, they were more focused on clinical care in the context of the pandemic, i.e., for the population presenting symptoms associated with lockdown and social distancing ( 40 42 ), while healthcare services for people with specific MD decreased during the pandemic. Healthcare institutions found it necessary to reduce inpatient and outpatient care processes to implement processes for the detection, monitoring and surveillance of COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning mental healthcare strategies, as reported in the literature, they were more focused on clinical care in the context of the pandemic, i.e., for the population presenting symptoms associated with lockdown and social distancing ( 40 42 ), while healthcare services for people with specific MD decreased during the pandemic. Healthcare institutions found it necessary to reduce inpatient and outpatient care processes to implement processes for the detection, monitoring and surveillance of COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, those most in need of mental healthcare are those whose livelihoods have been made even more precarious because of social disparities, in turn, few of them will seek help because their basic needs are not met by the mental healthcare systems ( 9 ). In contrast, a study in Brazil reported that, the reorganization of healthcare services integrating mental care is necessary to provide care access and continuity of care for people with MD ( 42 ).…”
Section: Discussionmentioning
confidence: 99%